Deu match! As trocas nos relacionamentos virtuais e a Objetificação do sujeito no Tinder - Cavalcanti, Hellen Taynam da Silva (2017)
The objective of this research was to analyze how the exchanges in the relationship applications collaborate to the objectification of the consumers in order to understand how the value can be co-created among the actors involved in this service. The netnographic research was developed in Tinder which is currently one of the most popular relationship applications in Brazil and worldwide. The data were collected through 19 interviews with Tinder consumers, carried out from May 2015 to November 2016, as well as the diary record with the main experiences that I lived in the application from October 2014 to December 2016. The Research results show that value co-creation has greater participation of users than the institution and the value of the application is attributed phenomenologically by the experiences in the exchanges. Relationship applications, in general, allow relationships between users analogous to consumer relationships and in Tinder, there is a sense that the next option may be more interesting favoring the accumulation of matches and the discarding of those that do not meet expectations, such as product that is returned by default. Research responds to social perspectives, specifically on the dynamics of relationships through connections; and managerial skills as you discuss possibilities for improvement in the application. It is concluded that in order to guarantee the value creation in the light of the Service- Dominant Logic, institutional control over the exchanges is necessary to avoid deviations in the use of Tinder. On the other hand, it must be considered that the dynamics that favor objectification is that which maintains the popularity of the application and any limitation of use, could cause Tinder to lose strategic benefits. In this case, it must be considered that the autonomy of cyberspace, in itself, requires institutional flexibility in regulations or even absence of them. So while some users have a negative perception of Tinder, others see opportunities to escape from the social routine with a lot of switching possibilities, and it is these uncontrolled exchanges that keep users active in the application and ensure their survival.